Das Drama von August Wilhelm von Iffland als Ausdruck des Identitätsproblems des deutschen Bürgers - Jurczyk, Ewa (Wydawnictwo Naukowe UAM, 1993)
This article discussed the tendencies of dramas of the popular drama writer in Germany at the turn of the 18th century. August Wilhelm Iffland, a representative of a trivial kind of bourgeois drama, the so called family drama. In the centre of his interests is the German burgher of this period who tries to establish his own position in the society. Iffland analyses social mechanisms - social, religious and cultural - which made it that the German burgher - passive and subordinated in public life attached greatest importance to the preservation of authority and the leading position in family life.